Advances in application of g–C3N4–based materials for treatment of polluted water and wastewater via activation of oxidants and photoelectrocatalysis: A comprehensive review. (January 2022) - Truong, Hai Bang; Bae, Sungjun; Cho, Jinwoo; Hur, Jin
Abstract: Recently, graphitic carbon nitride (g-C3 N4 ) has received significant attention as a non-metallic, visible-light-activated photocatalyst for treating water and wastewater by degrading contaminants. Accordingly, previous review articles have focused on the photocatalytic properties of g–C3 N4 –based materials. However, g-C3 N4 has several other notable features, such as high adsorption affinity towards aromatic substances and heavy metals, high thermal and chemical resistances, good compatibility with various materials, and easily scalable synthesis; therefore, in addition to simple photocatalysis, it can be widely used in other decontamination systems based on activation of oxidants and electrocatalysis. This critical review provides a comprehensive summary of recent advancements in g–C3 N4 –based materials and their use in treating polluted water and wastewater via the following routes (1) activation of oxidizing agents (e.g., hydrogen peroxide, ozone, peroxymonosulfate, and persulfate): and (2) photoelectrocatalysis using fabricated g–C3 N4 –based photocathodes and photoanodes. For each route, we briefly summarize the primary mechanisms, distinctive features, and performances of various water treatment systems using g–C3 N4 –based catalysts. We also highlight the specific roles of g-C3 N4 in improving the efficiencies of these treatment processes. The advantages and limitations of previously reported water treatment systems using g–C3 N4 –based materials are also described and compared in this review. Finally, we discuss the challenges and prospects of improving g–C3 N4 –based water purification applications. Graphical abstract: Image 1 Highlights: Recent advancements of g–C3 N4 –based materials in activation of oxidants and photoelectrocatalysis. Basic mechanisms, unique features, and performance of C3 N4 -based systems are investigated. Specific roles of g-C3 N4 in water treatment systems are discussed. Challenges and prospects for improving g–C3 N4 –based water purification are proposed.